High voltage gain bi‐directional Z‐source inverters with dual‐loop feed‐forward peak DC‐link voltage compensation for fuel cell vehicles. Issue 5 (24th December 2021) - Wang, Can; Yang, Dewei; Pang, Zhicong; Pan, Xuewei; Zhao, Fei
Abstract: High boost inverter is an essential part to interface the fuel cell stack and traction motor for fuel cell vehicles (FCVs). This paper proposes two novel high voltage gain bi‐directional Quasi‐ZSIs (QZSI) with new active switched inductor cells for FCVs application. The disadvantages of low voltage boost ratio, large start up current, unfavourable mode operations and unidirectional power flow in conventional Z‐source inverter (ZSI) are eliminated. The proposed Z‐source inverters are combined with active switched inductor cells to achieve a higher voltage gain and lower voltage stress over capacitors, which can be widely applied in energy storage systems. A small signal model is derived by dynamic analysis. In order to achieve a constant peak dc‐link voltage, a dual‐loop feed‐forward peak dc‐link voltage control strategy for the proposed QZSI is introduced in this paper. Simulation and experiment waveforms are presented to verify the theoretic analysis of the designed QZSIs and the proposed control strategy.